An effective dual-modification strategy to enhance the performance of LiNi0.6Co0.2Mn0.2O2 cathode for Li-ion batteries. Issue 8 (23rd February 2021) - Wang, Liang; Liang, Jiashun; Zhang, Xiaoyu; Li, Shenzhou; Wang, Tanyuan; Ma, Feng; Han, Jiantao; Huang, Yunhui; Li, Qing
Abstract : The dual-modification strategy of NCM622 cathode for Li-ion batteries could effectively relieve the interfacial instability and bulk structure degradation. Abstract : Ni-rich ternary layered oxides represent the most promising cathodes for lithium ion batteries (LIBs) due to their relatively large specific capacities and high energy/power densities. Unfortunately, their inherent chemical instability and surface side reactions during the charge/discharge processes lead to rapid capacity fading and poor cycling life, which seriously restrict their practical applications. Herein, we report a simple dual-modification strategy for preparing LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) cathode materials by Li2 SnO3 surface coating and Sn 4+ gradient doping. The gradient Sn doping stabilizes the layered structure due to the strong Sn–O covalent bond and relieves the Li + /Ni 2+ cation disorder by the partial oxidation of Ni 2+ to Ni 3+ . Besides, the ionic and electronic conductive Li2 SnO3 coating serves as a protective layer to eliminate the side reactions with electrolyte/air. In LIB testing, the dual-modified NCM622 cathode with 2% Sn delivers an enhanced cycling performance with 88.31% capacity retention after 100 cycles from 3.0 to 4.5 V at 1C compared to the bare NCM622. Meanwhile, the dual-modified NCM622 shows an improved reversible capacity of 136.2 mA h g −1 at 5C and enhanced electrode kinetics. The dual-modification strategy may enable a new approach to simultaneously relieve the interfacial instability and bulk structure degradation of Ni-rich cathode materials for high energy density LIBs.